Problem Based Training untuk Mereduksi Stres Akademik Mahasiswa pada Masa Pandemi - Suharni Suharni; Pratama Beny Dwi; Diana Vidya Fakhriyani (Edu Consilium : Jurnal Bimbingan dan Konseling Pendidikan Islam, 2022)
The purpose of this study was to determine the effectiveness of the application of problem based training in reducing student academic stress. The approach used in this research is an experimental approach, specifically Quasi Experimental Designs with a one-group pretest-posttest design. This study used a sample of 8 Guidance and Counseling Students who experienced high academic stress, with purposive sampling technique. The treatment used in this research is to use problem based training services. Data analysis technique using Wilcoxon test. The results showed that the application of problem based training services could reduce student academic stress.